Cognitive remediation therapy for forensic inpatients: a preliminary evaluation. (1st April 2016) - Marcer, Karen; Mills, Laura; Clarke, Caroline
Whilst there is an evidence base for cognitive remediation therapy (CRT) in severe mental illness, there is a paucity of research involving CRT for forensic inpatients. This study investigated the effectiveness of CRT in improving cognitive functioning in 13 patients in a low secure unit, including those with a history of substance misuse and/or head injury, a population which has typically been excluded from previous research. Outcome measures included the Hayling and Brixton tests, Digit Span (subtest of the Wechsler Adult Intelligence Scale) and the Zoo Map (subtest of the Behavioural Assessment of the Dysexecutive Syndrome). Improvements were demonstrated across the measures, with significant findings identified in six out of the eight measures. Reliable and clinically significant change analyses were conducted and indicated that CRT can provide both reliable and clinically significant change for forensic inpatients. Those with a history of head injury/ substance misuse demonstrated equal improvements. The findings indicate that CRT is an effective intervention for forensic inpatients, including those with co-morbid diagnoses of substance misuse/brain injury. Further research, including long term follow up is recommended.